Corticosterone Can Be an Essential Stress Index in Channel Catfish (Ictalurus punctatus) - Xiao, Kang; Wang, Xi; Liu, Wen-Bin; Zhang, Ding-Dong; Li, Xiang-Fei; Zhang, Chun-Nuan; Chen, Wei-Hua; Abasubong, Kenneth Prudence; Jiang, Guang-Zhen (Frontiers in Marine Science, 2021)
Although cortisol is considered the main glucocorticoid involved in regulating stress in fish by elevating the serum glucose, the presence of serum corticosterone and whether its level can be used as an indicator for fish stress activation and reflect the degree of fish stress remains to be determined. To comprehensively and accurately evaluate the performance of two glucocorticoids after stress, in this study, seven of the most common stressors (ammonia nitrogen, high-temperature, acid, alkali, Aeromonas hydrophila, and salinity) in aquaculture were selected. The levels of serum corticosterone, cortisol, and glucose were detected within 48 h, and then the dynamic changes were analyzed. In addition, the kidneys were collected to detect the expression of corresponding proteins involved in corticosterone and cortisol synthesis (3 β-HSD and CYP17A1) for further exploration. From the results obtained, the content of serum corticosterone was about 100 times higher than that of cortisol, and it was found that corticosterone and cortisol showed different dynamic changes within 48 h among the seven kinds of stress. In the subsequent detection of glucose, it was found that the dynamic shift in glucose was not consistent with the dynamic changes of corticosterone or cortisol entirely but seemed to be caused by the combination of the two. In the follow-up protein expression detection, we found that corticosterone seemed to respond to stress earlier. Therefore, it is concluded that the responses of corticosterone and cortisol to stress are independent, corticosterone may be more sensitive in the current seven acute stresses, and then they regulate glucose together to resist stress. The study aimed to fill the vacancy of corticosterone in fish research and provide a reference for the complete evaluation of fish stress degree.